Miguel Ontiveros: capstone - Ontiveros, Miguel, artist (Colorado State University. Libraries, 2014)
The artist's statement: A Closer Look & Forgotten Stories: We walk by hundreds of people every day, but how much do we really notice? At a glance, we all have the same features - eyes, a nose, a mouth - but it is the unique and intimate details in our faces that tell our stories. The individual differences and intricacies between people are often lost because of a lack of personal connection. I am interested in the personal connection that can be built between others with just one look. With the use of intimate closeness to the subject, I hope that others can connect to the faces of individuals and take the time to lose themselves in them, without a single spoken word. Biography: Born June 7, 1991 in Michoacán, Mexico. Miguel Ontiveros grew up in a small rural town called La Hermita. He lived in Michoacán until he was 9 years old when his mother decided that the part of Mexico in which they lived in was becoming too dangerous. They moved to Fort Collins where Miguel finished the rest of his education. Throughout his childhood Miguel had an un-understood passion for photography that was fully realized once he began attending Colorado State University in 2010.
Colorado State University Art Department capstone project.
Capstone contains the artist's list and images of works.
Keywords: photo image making